A multicentre verification study of the QuantiFERON®-TB Gold Plus assay. (January 2018) - Pieterman, E.D.; Liqui Lung, F.G.; Verbon, A.; Bax, H.I.; Ang, C.W.; Berkhout, J.; Blaauw, G.; Brandenburg, A.; van Burgel, N.D.; Claessen, A.; van Dijk, K.; Heron, M.; et al.
Abstract: Objectives: The aim of this verification study was to compare the QuantiFERON ® -TB Gold Plus (QFT-Plus) to the QuantiFERON ® -TB Gold In Tube (QFT-GIT). The new QFT-Plus test contains an extra antigen tube which, according to the manufacturer additionally elicits a CD8 + T-cell response above the CD4 + T-cell response. We assessed the value of this tube in detecting recent latent tuberculosis infections. Methods: Between May 2015 and December 2016, 1031 subjects underwent QFT-Plus and QFT-GIT test. Overall agreement between both tests and performance for different test indications and/or immune states was assessed. A difference of >0.6 IU/mL interferon-γ release between the two antigen tubes of the QFT-Plus assay was considered a true difference and used as estimation for CD8 + T-cell response. Results: Analysis of the QuantiFERON tests resulted in an overall agreement between assays of 95%. Subjects considered to be recently exposed to tuberculosis had significantly more often a true difference in interferon-γ release compared to all other subjects ( p = 0.029). Conclusion: Results of QFT-Plus are highly comparable to QFT-GIT. Although there is an indication that a true difference in interferon-γ release between the antigen tubes is associated with recent latent tuberculosis infection, the QFT-Plus could not be used to exclude recent exposure.